A study of a condolence letter decorated with bunches of flowers written by Raja Ali to Jan Jacob van Rochussen - Mu’jizah, (Universiti Kebangsaan Malaysia, 2008)
Malay letters have long been a source of illumination in Nusantara. For example a letter that was written by Raja Ali from Pulau Penyengat, Riau, in 1749 to Jan Jacob van Rochussen bears physical asthetics such as the patterns and various decorations that are not only beautiful but also unique. Two bouquets of flowers that consist of roses, sunflowers and chrysanthemums graced the motif that was used. Patterns were also made of flowers from the shrub tree and swastika signs. These decorations were also a source of information that was hidden in its symbolism. This paper will highlight the implicit meanings of these decorative symbols used in letters that carried the grave news of the death of King Willem. A description of the classical format used in these letters will be inserted into the analyses. A picture of the actual letter and transliteration of this letter will accompany this paper